1996
DOI: 10.1056/nejm199604043341403
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Acute Coronary Heart Disease — Mortality, Morbidity, Medical Care, and Risk Factors

Abstract: The recent decline in mortality due to CHD in the Minneapolis-St. Paul metropolitan area can be explained by both the declining incidence of myocardial infarction in the population and the improved survival of patients with myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
244
5
20

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 623 publications
(282 citation statements)
references
References 26 publications
13
244
5
20
Order By: Relevance
“…Details of the project are described in prior publications. 7,8 In brief, surveys are conducted approximately every 5 years in acutecare hospitals and the patient sample is based on an ICD-9 discharge diagnosis of AMI. The random selection of patient records is determined by computer and medical records are abstracted by trained nurses.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the project are described in prior publications. 7,8 In brief, surveys are conducted approximately every 5 years in acutecare hospitals and the patient sample is based on an ICD-9 discharge diagnosis of AMI. The random selection of patient records is determined by computer and medical records are abstracted by trained nurses.…”
Section: Methodsmentioning
confidence: 99%
“…3 This was in part the result of increased efforts to improve acute treatment and secondary prevention strategies. [3][4][5] In the acute phase AMI patients require rapid diagnosis and early reperfusion to minimise infarct size and to prevent complications. Several factors determine treatment delay with its major contributors being patient delay, physician delay and in-hospital delay.…”
mentioning
confidence: 99%
“…10 ED could therefore serve as a predictive symptom for potentially life-threatening CHD or stroke, both of which are leading causes of mortality in industrialized societies. 11 Two recent studies have suggested that ED represents an independent risk factor for future cardiovascular events, even independent of classic risk factors, such as diabetes and hypertension. 12,13 In 2005, we calculated the 10-year risk for CHD or stroke in a cohort of men with known International Index of Erectile Function (IIEF-5) score using the Framingham risk profile.…”
Section: Introductionmentioning
confidence: 99%